IDENTIFIKASI PROSES BERPIKIR KRITIS SISWA BERBASIS TUGAS PROYEK PADA SUBPOKOK BAHASAN PERSAMAAN LINIER SATU VARIABEL KELAS VII A SMPN 1 GLENMORE - Arfiansyah, Digga; Susanto, Susanto; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research described the process of critical thinking students based on project task for students with high mathematical ability, medium mathematical ability and low mathematical ability. The research is based on indicators critical thought process students by Jacob and Sam which includes phases of clarification, assessments, inference and strategy. Clarification, namely the stage where students formulate problems with precisely and clearly. Assessments, namely stage where the students find important question from problem. Inference, namely the stage where students make conclusion based on information that has been obtained. Strategy, namely the stage where students think in the open in resolving problems. This research using the instruments about the test projects and guidelines interview to obtain information deeper related to critical thinking students process. The results showed that subject with high mathematical ability of being through all stages of critical thinking process. To subject to medium mathematical ability being able to metamorphosis clarification, and inference assessments. To subject with low mathematical ability of being through all stages of critical tihinking process for first task, but not through strategy stages for second task. Keywords: Jacob and Sam Step, Critical Thinking Process, Project Task